Collaboration Between Islamic Education Teachers and Parents in Shaping Students' Character Through the MABIT Program - Haryono Idi; Askar Askar; Hamlan Andi Baso (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2026)
This study examines the collaboration between Islamic Religious Education (PAI) teachers and parents in shaping students’ moral character through the Malam Bina Iman dan Taqwa (MABIT) program at SD Islam Cahaya Khalifah Palu. The research employed a qualitative approach with exploratory and descriptive methods. Data were collected through field observations, interviews, and documentation involving PAI teachers, parents, and supporting stakeholders. The findings reveal that the collaboration was implemented systematically through the stages of planning, implementation, evaluation, and follow-up. The partnership between teachers and parents was strengthened through parenting programs, intensive face-to-face and digital communication, active parental participation, the use of communication books, and the involvement of religious and community leaders. The MABIT program not only functioned as a religious activity but also as an effective strategy for fostering students’ religious values, discipline, responsibility, and moral behavior both at school and at home. The study concludes that sustainable collaboration between schools and families plays a significant role in strengthening students’ character education in the contemporary educational context.